Proceedings of the Workshop on Stylistic Variation 2017
DOI: 10.18653/v1/w17-4909
|View full text |Cite
|
Sign up to set email alerts
|

Differences in type-token ratio and part-of-speech frequencies in male and female Russian written texts

Abstract: The differences in the frequencies of some parts of speech (POS), particularly function words, and lexical diversity in male and female speech have been pointed out in a number of papers. The classifiers using exclusively context-independent parameters have proved to be highly effective. However, there are still issues that have to be addressed as a lot of studies are performed for English and the genre and topic of texts is sometimes neglected. The aim of this paper is to investigate the association between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Gender differences: Due to the fact that there are gender differences in depression ( Murphy et al, 2000 ; Stordal et al, 2003 ; Herring and Paolillo, 2006 ; Johannsen et al, 2015 ; Klimusová et al, 2016 ; Rafi, 2019 ) as well as gender differences in text processing ( Litvinova et al, 2017 ) our analyses are conducted separately for men and women. We expect the results in each of the samples to differ in some features based on the gender of the writer.…”
Section: The Aim Of the Present Researchmentioning
confidence: 99%
“…Gender differences: Due to the fact that there are gender differences in depression ( Murphy et al, 2000 ; Stordal et al, 2003 ; Herring and Paolillo, 2006 ; Johannsen et al, 2015 ; Klimusová et al, 2016 ; Rafi, 2019 ) as well as gender differences in text processing ( Litvinova et al, 2017 ) our analyses are conducted separately for men and women. We expect the results in each of the samples to differ in some features based on the gender of the writer.…”
Section: The Aim Of the Present Researchmentioning
confidence: 99%
“…According to Litvinova et al (2016Litvinova et al ( , 2017, a lack of lexical diversity was associated with individuals with a greater likelihood of selfdestructive behavior, which may be useful to author profiling or personality identification systems.…”
Section: Lexical Diversitymentioning
confidence: 99%
“…Argamon et al (2003) has found that females use many more pronouns whereas males use noun specifiers more frequently in British National Corpus covering a range of genres. Litvinova et al (2017) has looked at the differences in the frequencies of some parts of speech (POS) between different genders in Russian written texts. Morphological features have shown to be important to discriminate between genders in many European languages (Mikros, 2013;Bortolato, 2016).…”
Section: Related Workmentioning
confidence: 99%